Controlled synthesis of sodium alginate electrospun nanofiber membranes for multi-occasion adsorption and separation of methylene blue - Wang, Qian; Ju, Junping; Tan, Yeqiang; Hao, Longyun; Ma, Yunliang; Wu, Yang; Zhang, Huawei; Xia, Yanzhi; Sui, Kunyan (Carbohydrate polymers, 2019)
•Three kinds of water-insoluble alginate-based nanofiber membranes were prepared.•The maximum actual adsorption capacity of nanofiber membranes can reach 2230 mg/g.•Separation experiment shows that separation efficiency reaches 97.33%.•Controlled synthesis membranes are applied to different adsorption environments. Herein, the three kinds of water-insoluble alginate-based nanofiber membranes were prepared by electrospinning and followed with crosslinking by calcium chloride (CaCl2), glutaraldehyde vapor (GA), and trifluoroacetic acid (TFA) crosslinking, respectively. All the sodium alginate(SA) nanofiber membranes present excellent integrated adsorption performance toward methylene blue (MB). Among these, CaCl2 crosslinked SA membranes exhibit the maximum actual adsorption capacity of 2230 mg/g and shortest adsorption equilibrium time of 50 min to date. On the basis of the selective adsorption of SA, the nanofiber membranes can separate MB/ methyl orange (MO) mixture solution and maintain high separation efficiency even after five cycles. In addition, respective applicable condition for differentially crosslinked SA nanofiber membranes was evaluated. The TFA crosslinked membranes have the least reduction in the adsorption capacity in acidic environment and GA crosslinked membranes adsorb better in alkaline environment. For seawater environment, GA crosslinked membranes show obvious adsorption performance than other crosslinked membranes.